2016
DOI: 10.21454/rjaic.7518/232.pec
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of perioperative complications in patients with and without obstructive sleep apnoea: a prospective cohort study

Abstract: Background and aims: Patients with obstructive sleep apnoea (OSA) have a high risk of postoperative complications. The purpose of the study was to record the spectrum and frequency of postoperative complications in patients with OSA versus (vs.) without OSA depending on the type of surgery and type of anaesthesia in a large cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…Subsequent studies 236 , 239 confirmed the previous findings, while 1 suggested benefits with regard to mortality. 239 Notably, in a prospective analysis investigating drivers of postoperative worsening of sleep-disordered breathing, Chung et al 79 demonstrated that the utilization of general anesthesia was associated with an increased central apnea index postoperatively, while 72-hour total opioid dose was a driver of increased AHI.…”
Section: Anesthesia Techniquesupporting
confidence: 63%
“…Subsequent studies 236 , 239 confirmed the previous findings, while 1 suggested benefits with regard to mortality. 239 Notably, in a prospective analysis investigating drivers of postoperative worsening of sleep-disordered breathing, Chung et al 79 demonstrated that the utilization of general anesthesia was associated with an increased central apnea index postoperatively, while 72-hour total opioid dose was a driver of increased AHI.…”
Section: Anesthesia Techniquesupporting
confidence: 63%
“…For simple dental surgery or procedures, local or regional anesthesia is preferred over general anesthesia. Postoperative outcomes may improve when regional anesthesia is used instead of general anesthesia [ 74 75 ]. For procedures requiring moderate sedation, pulse oximetry and/or capnography should be monitored for the early detection of airway obstruction or respiratory depression.…”
Section: Perioperative Managementmentioning
confidence: 99%
“… 10 12 However, others showed a significant difference in respiratory and cardiovascular complications in patients followed general anaesthesia compared with neuraxial anaesthesia and peripheral nerve blocks. 13 Besides, previous study showed that neither anaesthetic regimen (propofol/remifentanil vs sevoflurane/remifentanil anaesthesia) increased postoperative nocturnal obstructive and hypoxaemic episodes in patients with OSA following general anaesthesia. 11 In contrast, some studies suggested that propofol used alone or in combination with sevoflurane appears to be associated with more oxygen desaturations in children.…”
Section: Introductionmentioning
confidence: 96%